TOPIKAL APLIKASI FLUOR DALAM MENCEGAH KARIES GIGI PADA ANAK – SEBUAH LITERATURE REVIEW - Aldina, Ridha (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2024)
Maintaining oral and dental health is very important to achieve optimal body health, so it must start from the time of the primary teeth. The health of a child's primary teeth will determine the condition of the permanent teeth that will replace them. The most common dental and oral health problem is dental caries. Based on the results of Riskesdas data, the incidence of dental caries in Indonesia is still very high, so efforts and prevention of dental caries are needed. There are three types of prevention that can be done to prevent dental caries, namely primary, secondary and tertiary prevention. The earliest action is primary prevention. The main steps to prevent caries are effective for teeth that are still healthy or when initial caries occurs. Initial caries is characterized by demineralization of tooth enamel but no cavity formation. The primary stage of caries prevention includes dental health education, maintaining dental health, regular dental examinations, administering fissure sealants, and administering Topical Applications Fluoride (TAF). TAF is one of the most effective in preventing caries. TAF is a simple technique for application of fluoride solutions by dental practitioners and can be applied easily. This treatment is highly recommended for children who have just erupted in the mouth to strengthen the tooth enamel layer.